The Mysticism of Time and Space in Sufi Miracles Texts - Soleten, Wafek; Yossof, Batoul Ade (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The texts of Sufi miracles are full of unlimited richness regarding a mystic content of supernaturalism in relation to occurrences, characters, and tempo-spatial levels. Such a content has been a fertile environment for the manifestation of the mystical as based on a moment of reluctance to interpret the state of affairs as presented by the text of the Sufi various miracles in terms of tempo and spatial settings. In the texts of al-Nabhani, who collected the Sufi devouts' miracles, there is mystical richness of space and time interacting with the other structural elements; cause the breach of the laws of Time and Space would consequently lead into breaking the law of Action, and normal characters as well.